2010
DOI: 10.1002/dmrr.1140
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid polypeptide acts on glucose‐ stimulated beta cells to reduce voltage‐gated calcium channel activation, intracellular Ca2+ concentration, and insulin secretion

Abstract: glucose-stimulated islet beta-cell high voltage-gated calcium channels were activated in conjunction with insulin secretion, while high extracellular concentrations of IAPP inhibited beta-cell high voltage-gated calcium channel activation and insulin secretion in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…IAPP is produced by the beta cells [6] and co-secreted with insulin upon stimulation [7]. IAPP acts as a modulator for insulin release and reduces voltage-gated calcium channel activation and insulin secretion [8]. IAPP is synthesized as a 67 residues prohormone, and undergoes posttranslational processing to become biologically active.…”
Section: Introductionmentioning
confidence: 99%
“…IAPP is produced by the beta cells [6] and co-secreted with insulin upon stimulation [7]. IAPP acts as a modulator for insulin release and reduces voltage-gated calcium channel activation and insulin secretion [8]. IAPP is synthesized as a 67 residues prohormone, and undergoes posttranslational processing to become biologically active.…”
Section: Introductionmentioning
confidence: 99%
“…They found that VCCs were inhibited by high concentration of extracellular hIAPP, and they proposed that the reduction of GSIS in hIAPP-treated islets is the result of IAPP inhibition of VCCs (29). The mechanism was not described, but the authors suggested that it could also be involved in the activity of K ATP channels.…”
mentioning
confidence: 99%
“…However, the same final results would be achieved indirectly if hIAPP inhibits of the ATP-sensitive potassium channel (K ATP ) closure which would prevent the ␤-cell membrane depolarization required to induce Ca 2+ channel opening. This interesting problem was addressed by Soty et al [94] who, working with an hIAPP transgenic rat pancreatic ␤-cell line, found that membrane depolarization with 30 mM KCl, raises the intracellular Ca 2+ concentration and induces a very strong secretion of insulin, discarding the proposal that the reduction of GSIS in hIAPP-treated islets could be the result of hIAPP inhibition of voltage-gated Ca 2+ channels [93]. However it should be kept in mind that GSIS may be affected differently by hIAPP if it is added externally to islets or if it is overexpressed endogeneously in transgenic cells.…”
Section: Effect Of Hiapp On Plasma Membrane Channelsmentioning
confidence: 97%
“…Zhu et al [93] investigated the secretion of insulin in rat islet ␤-cells stimulated with a high glucose concentration (16.7 mM) in the presence or absence of externally added hIAPP. At the same time, they studied the activity of the high voltage-gated calcium channels and the intracellular calcium concentration.…”
Section: Effect Of Hiapp On Plasma Membrane Channelsmentioning
confidence: 99%